Quality management system in wood furniture industry in Malaysia - Chong, Yen Yoon (2015)
It is a general perceived that most globalized furniture manufacturing companies are often forced to seek ISO certification to improve quality. In this context, the fact that Quality Management Systems and Standards which were introduced in Malaysia since 1987, is often perceived to be a marketing tool within the exportled furniture manufacturing industry. However, many researchers reported that firms were not sure whether ISO certification managed to instill quality in their organizations. Although, there are more than 4,000 wood-based companies in Malaysia, with 125 of them being large furniture manufacturers and exporters, the portion of ISO registration within the industry is comparatively small compared to the total number of furniture companies. Therefore, this study was undertaken: (1) to determine the level of awareness of ISO 9001 certification among furniture buyers and level of certification among manufacturers in the Malaysia market; (2) to identify the major attributes and intentions of ISO 9001 certification among Malaysian furniture manufacturers; (3) to identify the drivers of ISO certification among furniture manufacturers; (4) to characterize the different furniture markets requirements and to compare the performance of ISO certified and non-certified suppliers of furniture in these markets; (5) to evaluate the reasons for adoption and non-adoption of ISO 9001 certification among furniture manufacturers; and finally (6) to identify the main benefits and challenges faced by ISO and non-ISO certified manufacturers from the furniture buyers’ perspective. The established relationship between ISO certification and product satisfaction, quality and the prevalence of repeat customers were used as the research framework for this study. Paired-sets of structured questionnaires were used to survey 100 foreign furniture buyers during the Malaysian International Furniture Fair (MIFF). For the Manufacturers’ perspective, 10 ISO and 20 non-ISO furniture manufacturers were surveyed. The result showed that manufacturers ranked quality improvement as the most important attribute. For respondents of ISO-certified manufacturers, the improvement on delivery time, quality and management were their major drivers to be ISO-certified. Nevertheless, the influence of the ISO system on product marketability is limited to specific markets, especially in Japan, Korea and East Asia, which are generally ISO-sensitive markets. On the other hand, the majority of the international furniture buyers were aware of ISO certification, and have requested their suppliers to be ISO-certified. ISO certification generally improves the overall performance of the furniture companies and large-scale companies have a greater tendency for ISO certification. Undoubtedly, ISO-certified suppliers provided higher satisfaction levels to customers, compared to non ISOcertified suppliers. For the buyers’ perspective, foreign furniture buyers prefer to purchase from ISO-certified companies, due to the higher degree of confidence in their business and product quality. This study shows that ISO certification had significantly influenced the management of furniture enterprises. The study also showed that the intention for ISO certification was not driven by external factors, neither the requirement of the governmental law and regulations nor the customer pressure, as most furniture manufacturers operated on the OEM strategy. Despite the benefits gained from higher market share, the low adoption level of the ISO system in the furniture sector could be explained by its high certification cost and lack of perceived benefits of certification among the furniture manufacturers. Finally, the study revealed that ISO certification is a useful tool to enhance the management competency within the furniture manufacturing sector. It appears that a concerted effort must be drawn up to boost the awareness of the intangible benefits to be gained, if ISO certification is to be expanded throughout the furniture industry in the future.